The efficiency of Caribbean stock markets - Arjoon, Vaalmikki (Central Bank of Barbados [St. Michael]BB, 2007)
Tests the weak-form efficiency of three major stock markets in the Caribbean region, the Trinidad and Tobago Stock Exchange (TTSE), Jamaica Stock Exchange (JSE) and the Barbados Stock Exchange (BSE). Concludes that the TTSE, JSE and BSE are characterised by weak-form efficiency.